Blended Learning in a Public Speaking Class: Integrating Canva Learning Management System with Face to Face Session (Conference on English Language Teaching, 2025)
This study aims to know how blended learning implemented in a university speaking class. The learning model combines Canva Learning Management System (LMS) with face-to-face meetings. The research used a qualitative method and involved 20 university students. Data were collected through interviews to understand students' opinions, experiences, and problems during the course. The results show that Canva LMS helped students to access learning materials easily. The materials were interesting and helped them practice speaking at home. Students said the LMS made learning more flexible and allowed them to study at their own pace. However, face-to-face classes were still very important. Students felt that speaking directly in class, getting feedback from the teacher, and interacting with friends helped them improve more. Some problems were also found. Others were not motivated to study by themselves or had trouble using the LMS at first. Teachers should also give more group tasks so that students can work and speak with each other more. This research shows that blended learning using Canva LMS and face-to-face sessions can help improve students' speaking skills if used in the right way.